Cultural Gateway Yogyakarta-Prambanan: Revitalisasi Berbasis Komunitas untuk Memulihkan Ekologi Interaksi Sosial di Pasar Tradisional Prambanan - Salsabil, Janitra Fullaroa (Gadjah Mada Journal of Tourism Studies, 2025)
Prambanan Traditional Market's strategic position within the Yogyakarta-Klaten cultural tourism corridor offers significant potential as a heritage tourism destination. However, its 2020 physical revitalization failed to enhance visitor engagement or the local economy due to neglecting socio-cultural practices that constitute the market's authentic identity. This study analyzes the causes of revitalization failure and develops a culture-led regeneration model through a Systematic Literature Review (PRISMA framework) of 30 journal articles (2014-2024) on Javanese markets and cultural tourism. Findings reveal that prioritizing physical modernization over intangible heritage degraded relational ecosystems—particularly meaningful bargaining rituals and ngalap berkah spiritual practices. Successful cases like Beringharjo Market preserved socio-spiritual interactions through community-driven governance. The research proposes the 3C Framework: Cultural Coding restores spatial philosophies enabling symbolic interactions; Community Co-Creation establishes cultural councils for participatory tourism curation; and Corridor Integration syncs market practices with heritage rituals through narrative trails. The framework reorients policies toward protecting intangible heritage via oral tradition schools and embedded cultural narratives, shifting paradigms from physical-centric approaches to cultural embodiment. This positions traditional markets as living heritage ecosystems where human relationality supersedes physical structures, transforming Prambanan into an authentic cultural gateway that sustains local economies through experiential tourism.